Quality indicators physical chemistry of wastewater of state Oaxaca, Mexico - Camacho-Ballesteros, Adriana; Ortega-Escobar, Héctor Manuel; Sánchez-Bernal, Edgar Iván; Can-Chulim, Álvaro (REVISTA TERRA LATINOAMERICANA, 2020)
The state of Oaxaca has an extensive and complex hydrological system due to its variation in regional and temporal availability. In addition, the human population and industrial growth have increased the discharge of wastewater, degrading its quality. The volume of wastewater that is allowed to be transferred into the channels of the State is 0.35 m3 s-1; however, there are illegal discharges that increase the ionic concentrations; these waters are used for agricultural irrigation from its source to its mouth. In order to quantitatively assess the parameters over ionic concentrations of wastewater to be applied in agricultural soils, 89 sampling stations were established in the summer of 2018 along the State. The water quality was classified according to its electrical conductivity (EC), sodium adsorption ratio (RAS), residual sodium carbonate (CSR), and concentration of boron and phosphorus. The coefficient of mg L-1 = af (EC) was a = 0.671, this value a corresponds to the type of water of SO4‑Cl‑HCO3 composition. The pH was 6.98-7.54-8.32; the EC fluctuated between 80 and 2550 µS cm-1 with an average value of 475 μS cm-1. The content of Na2CO3 is (-0.34) -0.74-8.10 mmolc L-1. The coefficient of the functional relationship μ (M L‑1) = af (EC) was a = 0.0117. The values of original, adjusted and corrected RAS were: RASor 0.27-1.82-11.54, RASaj 0.05-2.76-23.51 and RAScorr 0.18-1.87-12.66, respectively. To determine the potential danger of sodicity, PSI-RAS relationship values were calculated, resulting in RASor = 16.32, RASaj = 28.43, RAScorr = 17.63. In accordance with the physical-chemical parameters, the wastewaters from Oaxaca are sulphatic-hydrochloric-bicarbonated.